2019
DOI: 10.22462/01.03.2019.2
|View full text |Cite
|
Sign up to set email alerts
|

Cold water submersion attenuates post-submersion aerobic performance and orthostatic tolerance irrespective of partial rehydration with water

Abstract: Purpose: This study examined the independent effects of cold-water submersion and a rehydration strategy on an aerobic endurance performance and orthostatic tolerance following a four-hour dive in cold water (10°C). Methods: Nine male subjects completed a control (CON) performance and lower-body negative pressure test (LBNP) and two water immersion visits with either no rehydration (NR) or a post-immersion rehydration (RH) with 1 L of water. Following submersion, subjects ran to exhaustion and submitted to LBN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Postimmersion running performance (.70% V Ȯ2max ) is reduced in a temperate environment with ;2% immersion-induced hypohydration (10,11). The compromising effects of dehydration were expected to be augmented with cold-water immersion and exercise in a warm environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postimmersion running performance (.70% V Ȯ2max ) is reduced in a temperate environment with ;2% immersion-induced hypohydration (10,11). The compromising effects of dehydration were expected to be augmented with cold-water immersion and exercise in a warm environment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in our laboratory has shown that 4 hours of thermoneutral water immersion results in mild hypohydration (∼1.6% body mass loss) and that fluid replacement during or following water immersion has no effect on run time to exhaustion at 70% age-predicted heart rate max (11). In a similar study, 4 hours of cold-water immersion (10°C) resulted in >2% body mass loss and a 23% reduction in run time to exhaustion at ∼85% maximal oxygen consumption (V̇O 2max ) in thermoneutral conditions compared with a no-immersion control (10). Postimmersion fluid replacement (1 L of water) failed to rescue these performance decrements despite correcting body mass loss to ∼0.8% of baseline.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation